FINANCIAL AND DIGITAL MARKETING LITERACY TRAINING TO INCREASE ENTREPRENEURSHIP INTENTION IN MALANG KNITTING COMMUNITY: PELATIHAN LITERASI KEUANGAN DAN DIGITAL MARKETING UNTUK MENINGKATKAN MINAT WIRAUSAHA PADA KOMUNITAS RAJUT MALANG - Ajeng Rachma Pertiwi; Rindah Febriana Suryawati; Ditya Permatasari; Elsha Sophia (Darmabakti Cendekia: Journal of Community Service and Engagements, 2024)
Background: Malang Knitting Community (KRM) is a community of knitting women in Malang City, Indonesia which is facing a problem of a lack of financial literacy, especially regarding how to prepare financial statements and digital marketing of each community member. Objective: This activity aims to provide financial literacy and digital marketing training for KRM members to increase interest in starting a business. Method: This community service provided in-class offline training on the topics of financial literacy and digital marketing and followed by coaching in preparing financial reports. The impact evaluation was conducted through discussions with KRM members regarding the success of the program. Results: After training and coaching, the number of respondents interested in starting a business increased from 30% to 100% and they understood and were able to prepare a simple financial statement. Conclusion: The training and coaching activities on the topics of financial literacy and digital marketing provide positive benefits to KRM members. Similar activities are still very relevant to be carried out in various communities.